2015
DOI: 10.1039/c5nr03472h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical fabrication and characterization of Cu/Cu2O multi-layered micro and nanorods in Li-ion batteries

Abstract: Electrodes composed of freestanding nano- and microrods composed of stacked layers of copper and cuprous oxide have been fabricated using a straightforward one-step template-assisted pulsed galvanostatic electrodeposition approach. The approach provided precise control of the thickness of each individual layer of the high-aspect-ratio rods as was verified by SEM, EDS, XRD, TEM and EELS measurements. Rods with diameters of 80, 200 and 1000 nm were deposited and the influence of the template pore size on the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…As this amount corresponds to a deposition charge of 1.39 C while the experimental deposition charge was 1.16 C, it is clear that there also must have been lithium ions in the sample mainly due to the Cu 2 O conversion reaction (i. e. Cu 2 O + 2 Li + + 2 e − =2 Cu + Li 2 O). Since the total reduction charge for the voltammetric scan and the potential step was 2.05 C, the extra reduction charge, which mainly was associated with the large reduction peak at about 0.8 V vs. Li + /Li, was about 0.89 C. The latter is very close to the 0.9 C expected for a native Cu 2 O coating on a 50 cm 2 Cu substrate since the capacity for the Cu 2 O conversion reaction has been found to be about 5 μAh cm −2 . It can therefore be concluded that the peak at about 0.8 V vs. Li + /Li in Figure A mainly was due to the reduction of Cu 2 O.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…As this amount corresponds to a deposition charge of 1.39 C while the experimental deposition charge was 1.16 C, it is clear that there also must have been lithium ions in the sample mainly due to the Cu 2 O conversion reaction (i. e. Cu 2 O + 2 Li + + 2 e − =2 Cu + Li 2 O). Since the total reduction charge for the voltammetric scan and the potential step was 2.05 C, the extra reduction charge, which mainly was associated with the large reduction peak at about 0.8 V vs. Li + /Li, was about 0.89 C. The latter is very close to the 0.9 C expected for a native Cu 2 O coating on a 50 cm 2 Cu substrate since the capacity for the Cu 2 O conversion reaction has been found to be about 5 μAh cm −2 . It can therefore be concluded that the peak at about 0.8 V vs. Li + /Li in Figure A mainly was due to the reduction of Cu 2 O.…”
Section: Resultssupporting
confidence: 66%
“…The Li electroplating was performed on 3D Cu substrates,, featuring Cu nanorods coated with a thin native Cu 2 O oxide layer. In Figure , which shows the two‐step Li electrodeposition approach, it is seen that the potential initially was scanned from the OCP of 3.1 to −0.25 V vs .…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations